Analisis Kemajuan Digitalisasi Agro Eduwisata Padi Organik di Desa Mulyaharja - Imam Hanif Aqeela; Elchio Fajar Hisra; Muallifah Shofiatun; Vemita Joselfyn; Putri Nurul Hidayah; Siti Zahra Levina; Ravael Nariyan; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
"Digitalization Web for Mulyaharja Village, Bogor: A Community Empowerment Initiative" This project aims to develop a digital platform for Mulyaharja Village, Bogor, to enhance community empowerment and improve access to information and services. The web-based platform will provide a range of features, including news and announcements, community forums, and online services, to facilitate communication and collaboration among residents, village officials, and local businesses. By leveraging digital technology, this initiative seeks to promote transparency, accountability, and inclusivity in village governance, while also fostering economic growth and social development.